2015
DOI: 10.1515/helmin-2015-0034
|View full text |Cite
|
Sign up to set email alerts
|

Serological survey for canine angiostrongylosis in Slovakia

Abstract: SummaryIn recent years Angiostrongylus vasorum has become another important heart parasite of dogs besides Dirofi laria immitis, with intense spread into new areas of Europe. The fi rst two cases of canine angiostrongylosis in Slovakia were observed in 2013, demonstrating that this life-threatening parasitic disease of dogs has expanded into this territory too. One year after the fi rst A. vasorum fi ndings, a serological survey was conducted to assess the current distribution of this parasitic infection in do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…This study has confirmed once again the applicability of serological methods in large-numbers epizootiological studies and investigations on pet metastrongyloid angiostrongylids [ 47 , 50 , 51 , 132 , 133 , 134 , 135 ]. The usefulness of serology should be considered in planning future studies relying on standardized methods towards comparable results from different regions and settings.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This study has confirmed once again the applicability of serological methods in large-numbers epizootiological studies and investigations on pet metastrongyloid angiostrongylids [ 47 , 50 , 51 , 132 , 133 , 134 , 135 ]. The usefulness of serology should be considered in planning future studies relying on standardized methods towards comparable results from different regions and settings.…”
Section: Discussionsupporting
confidence: 75%
“…As in previous studies, the number of dogs with detectable A. vasorum Ab was here higher if compared to the number of dogs showing circulating Ag [ 8 , 47 , 50 ]. Many reasons can account for this discrepancy, e.g., the inclusion of dogs (i) sampled during prepatency when Ag is not detectable yet, (ii) after a natural clearance of the infection (iii) after antiparasitic treatment, based on longer persistence of Ab [ 51 , 52 ].…”
Section: Discussionsupporting
confidence: 74%
“…Germany, bordering northwesterly, is the one with long-standing reports of A. vasorum cases (Pallaske 1967;Eckert and Lämmler 1972) and several epidemiological studies confirmed its presence in particular in the south-eastern part of Germany (Taubert et al 2008;Barutzki and Schaper 2009;Schnyder et al 2013a). Further recent studies report A. vasorum from Poland (Schnyder et al 2013b;Demiaszkiewicz et al 2014), bordering northerly to the Czech Republic, and from Slovakia (Hurnikova et al 2013;Miterpakova et al 2015), bordering easterly.…”
mentioning
confidence: 92%
“…Moreover, new autochthonous cases have been described in other countries such as Belgium [ 21 ], Slovakia [ 22 ] and Serbia [ 23 ]. During the past years, it has been possible to obtain a more complete picture of parasite prevalence in dog populations through large scale serological studies carried out in some countries, for example in Germany and UK [ 24 ], Italy [ 25 ], Switzerland [ 26 ], Poland [ 27 ], Hungary [ 7 ], Slovakia [ 28 ], Bulgaria [ 29 ], Belgium [ 30 ] and Portugal [ 31 ].…”
Section: Introductionmentioning
confidence: 99%